2010
DOI: 10.1586/eem.09.70
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in signaling pathways in diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is characterized by a plethora of signaling abnormalities that together ultimately result in the clinical and pathologic hallmarks of DN, namely progressive albuminuria followed by a gradual decline in glomerular filtration rate leading to kidney failure, and accompanied by podocyte loss, progressive glomerular sclerosis and, ultimately, progressive tubulointerstitial fibrosis. Over the past few years, the general understanding of the abnormalities in signaling pathways that lead to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 145 publications
1
85
0
1
Order By: Relevance
“…Pearson's test in the experimental groups revealed statistically significant correlations of renal NF-κB staining with the urine albumin-tocreatinine ratio (r=0.515, p=0. key pathogenic mechanisms and intracellular pathways leading to progression of diabetes complications are not modified by the current therapies [11,20]. Herein, we report that a cellpermeable peptide derived from the IKKα/βNBD domain inhibits the canonical NF-κB pathway and ameliorates renal dysfunction and atherosclerosis in diabetic mice primarily through the attenuation of local and systemic inflammation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Pearson's test in the experimental groups revealed statistically significant correlations of renal NF-κB staining with the urine albumin-tocreatinine ratio (r=0.515, p=0. key pathogenic mechanisms and intracellular pathways leading to progression of diabetes complications are not modified by the current therapies [11,20]. Herein, we report that a cellpermeable peptide derived from the IKKα/βNBD domain inhibits the canonical NF-κB pathway and ameliorates renal dysfunction and atherosclerosis in diabetic mice primarily through the attenuation of local and systemic inflammation.…”
Section: Resultsmentioning
confidence: 97%
“…Clinical and experimental evidence implicates NF-κB activation and regulated genes in the early phases, progression and final complications of diabetes and, as such, its inhibition offers therapeutic intervention opportunities [11][12][13][14][15][16][17]. Although several NF-κB inhibitors have reached phase II/III clinical trials for inflammatory diseases [18,19], most research into cardiovascular or renal diseases is only in the preliminary experimental phase [20].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by glomerular mesangial expansion caused by mesangial cell hypertrophy, followed by extracellular matrix protein accumulation and subsequent glomerulosclerosis (1)(2)(3)(4). Cellular hypertrophy, a maladaptive increase in total cell volume and protein content without a concomitant increase in total cell number, is one of the early abnormalities found in DN (5).…”
Section: Diabetic Nephropathy (Dn)mentioning
confidence: 99%
“…Liu et al (18) have demonstrated that STAT3 and JAK3 may act together, with JAK activation determining STAT activation, when investigating therapeutic effects of some cytokine inhibitors in diabetic nephropathy. There is other evidence that the JAK/STAT pathways act in diabetic nephropathy and may provide novel targets for new therapies (21)(22)(23). In this study, activated STAT3 (pSTAT3) expression was negligible in fibroblast and epithelial cell cultures treated with H 2 O 2 and so again little explanation was found for the discrepancies in JAK3 mRNA and protein after oxidative stress.…”
Section: Discussionmentioning
confidence: 59%